Elaboración e Implementación de un Modelo de Gestión Administrativa – Financiera para la “Corporación de Pequeños y Medianos Emprendedores Nueva Vida de Chimborazo”, de la ciudad de Riobamba y su impacto en los indicadores de gestión en el periodo marzo – diciembre 2013. - Tapia Bonifáz, Angelita Genoveva (2014)
This research entitled "Development and Implementation of a Model of Administrative Management-Finance for the" Corporation of Small and Medium Entrepreneurs Chimborazo New Life ", the city of Riobamba and its impact on management indicators in the period March-December 2013 ". Which is based on the Administrative and Financial Handbook leaning on the stage of the administrative process that allowed structure and guide in this specific case to the Corporation, but the manual that has been made and implemented can be adapted to any similar organization in same constant suggestions, steps must be taken into account as well as administrative and financial formats, with a chart of accounts which helps to better development of activities and actions for verification of results. A methodology that began with a SWOT matrix, through which a diagnosis of administrative management and financial determining internal and external factors that allowed obtaining weights to determine their potential and go identifying weaknesses of the corporation with reliable data to be performed was, (comma out) applied discussing the topic of investigation. In the analysis of survey results was used to partners and people working in the corporation to see if the application of the manual has consented organizational strengthening, taking into account management indicators. After implementing the manual partners and corporate clients responded that errors were corrected, as was evident in surveys that 53% believe that the services of the corporation are good, 20% consider it very good. According to the results of financial indicators have increased the usefulness of 7.16% over the previous year; for every dollar they had as service revenue in 2013 increased by 9% had; we can narrow (or refine) to others that for every dollar invested in the asset has a cost of 0.29 cents. In the proof of the hypothesis is concluded that the development and implementation of the management model has allowed evaluating the impact of management indicators in the corporation; allowing making timely and effective decisions to improve their service.